Teratogenic Effects of Antiepileptic Drugs - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Data from 5 prospective European studies totaling 1,221 children exposed to antiepileptic drugs (AED) during pregnancy and 158 children of unexposed control pregnancies were analyzed to quantify the risk of major congenital malformations (MCM) and are reported from University Medical Centers in Rotterdam and Heemstede, The Netherlands; Berlin and Magdeburg, Germany; and Helsinki, Finland.